2021
DOI: 10.1039/d1ra01373d
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4@Sap/Cu(ii): an efficient magnetically recoverable green nanocatalyst for the preparation of acridine and quinazoline derivatives in aqueous media at room temperature

Abstract: A highly efficient, robust, and green protocol has been developed for the synthesis of acridine and quinazoline derivatives in water under mild reaction conditions using a Fe3O4@Sap/Cu(ii) nanocomposite as an efficient heterogeneous catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…Sulfated zirconium oxide was prepared according to a previously reported procedure. 23,24 First, to a solution of 2.3 g of ZrCl 4 (as a precursor) in distilled water (10.0 mL), 10.0 mL of 1.0 N ammonia solution was added dropwise during a span of 30 min to the solution until the solution pH was adjusted to 11.0. The milky solution was aged for a day at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Sulfated zirconium oxide was prepared according to a previously reported procedure. 23,24 First, to a solution of 2.3 g of ZrCl 4 (as a precursor) in distilled water (10.0 mL), 10.0 mL of 1.0 N ammonia solution was added dropwise during a span of 30 min to the solution until the solution pH was adjusted to 11.0. The milky solution was aged for a day at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon has also been observed for cross-linked catalysts. [48][49][50][51] In other words, in the ltration method, only a part of the reaction mixture in contact with the catalyst surface intends to pass through the catalyst, and this issue increases the effective concentration at the catalyst surface and increases the efficiency. This experiment also showed that the ltration method, as a new and portable method, has an advantage over the heterogeneous method (cutted paper).…”
Section: Screening Of the Reaction Parametersmentioning
confidence: 99%
“…[165] Heterogeneous catalysts have their own importance in terms of easy recovery by simple filtration and reusability. [166,167] Several easily recoverable and recyclable catalysts have been utilized for the synthesis of acridine-1,8-diones with high to excellent yields for illustration Fe 3 O 4 @Sap/Cu(II) [168] Pt NPs@graphene oxide [169,170] Au/NiAlTi layered double hydroxide nanocatalyst, [171] functionalized multi-walled carbon nanotubes (f-MWCNT) [172] and silica-supported metal NPs. [173][174][175][176] Scheme 21.…”
Section: Synthesis Of Acridine-18-dione Derivativesmentioning
confidence: 99%